Happy 70th Birthday Professor Miller - Miller, Lejla (Sarajevo Journal of Mathematics, 2024)
This issue of our journal is devoted to our editor in chief Professor Harry I. Miller on the occasion of his 70th birthday. Many authors, his colleagues and former students, have contributed to this edition, dedicating their papers to Professor Miller. Unfortunately, due to a delay in the refereeing process, the work of one of our Editors, Professor Mirna Dˇzamonja, submitted for this edition, will have to appear in a latter edition.